Camping Equipment Recommendation System Using Content-Based Filtering Method: A Case Study of Berkah Outdoor45 - Nugroho, Robby Gusti; Sumarlinda, Sri; Srirahayu, Agustina (International Journal Software Engineering and Computer Science (IJSECS), 2024)
Camping is a favorite activity for various age groups carried out in the open air to enjoy the beauty of nature and get away from the noise of the city. The high cost of camping equipment encourages many people to prefer renting rather than buying, making Berkah Outdoor45 the main choice for nature lovers to rent camping equipment. This study aims to develop a recommendation system for selecting camping equipment using a content-based filtering mechanism with a TF-IDF approach to help users choose equipment that suits their needs. This study uses a waterfall system development model which includes the stages of analysis, design, implementation, and testing. Testing is carried out using the Blackbox method to evaluate the effectiveness of the system. The results showed that from 18 datasets, the system can provide four recommendations with the highest similarity values, namely D11 (0.377), D18 (0.354), D2 (0.320), D5 (0.311), and D1 (0.287) based on a predetermined formula. The recommendation system developed successfully provided accurate recommendations that were in accordance with user preferences, while reducing ordering errors and increasing efficiency in selecting camping equipment.